Peran Unit Pelaksana Teknis Kesatuan Pengelolaan Hutan Saddang II dalam Melestariikan Hutan Lindung di Kabupaten Toraja - Nurlaila, Nurlaila; Fatmawati, Fatmawati; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine the role of Saddang II Forest Management Unit in protecting proted forests in North Toraja Regency. This study used Qualitive with data and secondary data, as many as 11 research informants, data collection techniques used observatiaon and interview guidelines. The results of the study showed that the role of the Unit of Saddang Forset Management Unit II had not yet fully run well, this could be seen from the aspect of lack of communication between the Unit of Forest Management Unit with Communities related to forest protection activites and the absence of counseling/socialization conducted by the Unit of Saddang Forest Management Unit II towards the community.